Postoperative conformal radiotherapy of locally advanced squamous-cell oropharyngeal cancer - N. V. Kanishcheva; D. V. Sikorsky; D. V. Skamnitsky; К. V. Bazanov; A. V. Maslennikova; S. О. Podvyaznikov (Опухоли головы и шеи)
The study objective is to demonstrate the necessity of individual selection of radiation plan in patients with locally advanced squamous-cell oropharyngeal cancer after multicomponent operation to decrease radioreactions and radiation injuries.Materials and methods. The study included data on 64 patients with primary locally advanced oropharyngeal cancer after combination treatment at the Nizhny Novgorod Regional Clinical Oncological Dispensary in 2013–2018.  Radiation treatment was performed after surgeries. The 1st group included 30 patients who underwent conformal radiation using linear accelerators. The 2nd  group included 34 patients who underwent conventional radiation.Results. For conformal radiotherapy, grade I mucositis was observed in 2 (6.6 %) patients, grade II – in 25 (83.4 %) patients, grade III– IV – in 3 (10 %) patients. In the 1st group, radioreactions developed at dose 30 Gy, in the 2nd group at 20 Gy. In the 2nd group, radioreactions were more severe. Grade II mucositis after conventional radiation were observed in 21 (61.7 %) patients, grade III–IV – in 13 (38.3 %) patients, among them 8 (23.5%) received split-course radiotherapy. Partial necrosis of the flap was detected in 1 (3.3 %) patient in the 1st group and in 4 (2.9 %) patients in the 2nd group.Conclusion. Conformal radiotherapy, including modulated intensity, is characterized by better isodose distribution with minimal effect on the surrounding healthy tissue and vascular pedicle of the transplant after multicomponent operations. This type of radiation allows to decrease the risk of radioreactions and complications requiring expensive accompanying therapy or even split-course treatment.